ThoroughFare atrial pressure controller device to create a controlled interatrial right-to-left shunt in advanced pulmonary arterial hypertension – A pilot study - Bojja Venkata Satya Roopesh; Girija Haritha; S. V. Kishore; Muthukumaran Chinnasamy Sivaprakasam; Shreesha Maiya; Saileela Rajan; Pramod Sagar; Kothandam Sivakumar (Annals of Pediatric Cardiology)
Background: Atrial flow regulators are used in patients with pulmonary arterial hypertension (PAH) who present with syncope or advanced heart failure. The ThoroughFare atrial pressure controller (Meril Life Sciences, Vapi, India) is a new device for similar use. The differences in structural design include a cable–screw release mechanism and a low profile. Methods: A multi-institutional study assessed the feasibility and safety of this device and reported short-term follow-up. This device, with an 8-mm fenestration diameter, was deployed after transseptal puncture using a 12F sheath. Results: Between April 2023 and June 2024, 15 symptomatic patients aged 5–39 years, including four children, received this implant after dual pulmonary vasodilator pharmacotherapy for at least 2 years. Etiology included idiopathic PAH in eight patients, hereditary PAH in two, operated shunt lesions in four, and human immunodeficiency virus-associated PAH in one patient. The key indication was recurrent syncope in 11 and right heart failure in the rest. The mean N-terminal pro-brain natriuretic peptide was 2414 ± 2046 pg/mL. The hemodynamic assessment revealed high right atrial pressures in 80% of patients, low cardiac index in half, and suprasystemic pulmonary pressures in four patients. The procedure was completed in all patients without any complications. Pulse oximeter saturations dropped from 98% ±2% to 92% ±4%. Symptoms improved over a median follow-up of 8 months, and the device patency was confirmed in all patients except one patient who died 5 months postprocedure after a heart–lung transplantation. Conclusion: ThoroughFare atrial pressure controller implantation was feasible and safe for all patients with severe PAH without any complications. Longer follow-up with more patients is needed to ascertain the functional improvements.